Analisis Tingkat Kapasitas Aparatur Pemerintah Desa - Sitti Aminah; Hari Prasetyo Sutanto (Research and Development Agency Ministry of Home Affairs, 2018)
The lack of capacity of the village apparatus causes the implementation of government, development and community services not optimal. The purpose of the study is to analyse the level of capacity of village government officials on of knowledge, attitudes and skills aspects. Data were collected in August and September 2016 in Bogor Regency and used descriptive statistics analysis. The study result shows that village apparatus capacity is inadequate on the aspects of village government management, village development planning, village financial management and addressing village problems. The study recommendations are to increase learning to village officials through training, mentoring and intensive socialization of village government regulations.